Access to Knowledge in Brazil New Research on Intellectual Property, Innovation and Development - Shaver, Lea (Access to Knowledge, 2010)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. "Brazil is one of the world's most productive crucibles for new ideas and practices in innovation and collaboration. This meticulously researched book provides a sweeping tour of the issues arising form that leadership." Jonathan Zittrain - Professor, Harvard Law School "As policy makers around the world grapple with how to configure their intellectual property policies to promote innovation and economic growth, as well as public access to the fruits of intellectual labour, they would do themselves a huge favour by reading Lea Shaver's excellent book." Pam Samuelson, Professor Univeristy of California, Berkeley "This is essential reading for anyone who cares about one of the most important human rights issues of the century: access to knowledge." Madhavi Sunder, Professor of Law, University of California Davis This volume features four chapters addressing the current issues facing intellectual property, innovation and development policy in Brazil. Each chapter is authored by legal scholars affiliated to the Fundação Getulio Vargas law schools in São Paulo and Rio de Janeiro. Each chapter examines a policy area that significantly impacts access to knowledge in Brazil. These include: exceptions and limitations to copyright, free software and open business models, patent reform and access to medicines, and open innovation in the biotechnology sector.